An estimate for the modulus of continuity of a quaternion singular Cauchy integral - Gerus, O. F. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We establish an upper bound for the modulus of continuity of a quaternion singular Cauchy integral in terms of the modulus of continuity of the integrand and a metric characteristic of a curve.